1994
DOI: 10.1111/j.1476-5381.1994.tb13126.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the new A2 adenosine receptor antagonist 8FB‐PTP, an 8 substituted pyrazolo‐triazolo‐pyrimidine, on in vitro functional models

Abstract: 1 We have characterized the in vitro pharmacological profile of putative A2 adenosine antagonists, two non-xanthine compounds, 5-amino-8-(4-fluorobenzyl)-2-(2-furyl)-pyrazolo [4,3-e]-1,2,4-triazolo[l ,5-c] pyrimidine (8FB-PTP) and 5-amino-9-chloro-2-(2-furyl 1,2,4-triazolo [1,5-c] quinazoline (CGS 15943), and the xanthine derivative (E)7-methyl-8-(3,4-dimethoxystyryl)-1,3-dipropyl-xanthine (KF 17837).2 In binding studies on bovine brain, 8FB-PTP was the most potent (Ki = 0.074 nM) and selective (28 fold) dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In addition to its limited selectivity in functional studies, the lack of information of activity of 8-(3-chlorostyryl)-1,3-dipropyl-xanthine at A2b receptor subtypes (Jacobson et al, 1993) A2a selectivity in functional assays (Dionisotti et al, 1994). ZM 241385 had 30-80 fold selectivity for A2a over A2b receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its limited selectivity in functional studies, the lack of information of activity of 8-(3-chlorostyryl)-1,3-dipropyl-xanthine at A2b receptor subtypes (Jacobson et al, 1993) A2a selectivity in functional assays (Dionisotti et al, 1994). ZM 241385 had 30-80 fold selectivity for A2a over A2b receptors.…”
Section: Discussionmentioning
confidence: 99%
“…CGS 1 5943 (5-amino-9-chloro-2 -(2-furyl)-pyrazolo-[4,3 -e]1,2,4 -triazolo [1,5-c]quinazoline) has high affinity for the A2a receptor (Ki 3 nM) but modest A2a: Al selectivity (7 fold) (Williams et al, 1987). Dionisotti et al (1994) (Williams et al, 1986), rat cloned A3 receptors expressed in chinese hamster ovary cell line (Olah et al, 1994) and in rat cortex (Bruns et al, 1987a) respectively. Evaluation of antagonism of adenosine receptor-mediated responses was further investigated in guinea-pig atria (Al receptor, Collis, 1983), guinea-pig Langendorff hearts (A2a receptor, Ueeda et al, 1991) and guinea-pig isolated aortae (A2b receptor, Hargreaves et al, 1991;Martin, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 As a result, we propose that the absence of protection seen in PC dogs treated with CGS is a consequence of poor patency (prolonged duration of ischemia) that is due to the inhibition of platelet A 2 receptors. However, this conclusion is confounded by the fact that PC-induced cardioprotection is initiated by stimulation of adenosine A 1 /A 3 receptors on myocyte membranes, 2 and CGS, despite its nanomolar affinity for the A 2 receptor, is not subtype specific 12,13 ; ie, the loss of protection seen in PC dogs that received CGS could be due in part to residual A 1 receptor antagonism on myocytes.…”
Section: Loss Of Cardioprotection With Cgs: Poor Patency or A 1 Inhibmentioning
confidence: 99%
“…We observed no deleterious changes in patency, consistent with ex vivo evidence showing CGS to be devoid of intrinsic effects on platelet aggregation. 12,13 An explanation for the poor patency in CGS-treated dogs may be derived from evidence from a canine model of hypoperfusion, which showed that maintenance of stable coronary blood flow is dependent on endogenous adenosine; ie, infusion of a nonselective adenosine receptor antagonist initiated a progressive deterioration in coronary perfusion that was due to the formation of platelet thrombi. 7,8 Thus, even in non-PC controls, adenosine may participate in the regulation of platelet activity and coronary patency.…”
Section: Deleterious Effect Of Cgs On Coronary Patency?mentioning
confidence: 99%
See 1 more Smart Citation